Biomolecular condensates at sites of DNA damage: More than just a phase(☆,☆☆) - Spegg, Vincent (2021)

(untitled) (DNA Repair (Amst))
Protein recruitment to DNA break sites is an integral part of the DNA damage response (DDR). Elucidation of the hierarchy and temporal order with which DNA damage sensors as well as repair and signaling factors assemble around chromosome breaks has painted a complex picture of tightly regulated macromolecular interactions that build specialized compartments to facilitate repair and maintenance of genome integrity. While many of the underlying interactions, e.g. between repair factors and damage-induced histone marks, can be explained by lock-and-key or induced fit binding models assuming fixed stoichiometries, structurally less well defined interactions, such as the highly dynamic multivalent interactions implicated in phase separation, also participate in the formation of multi-protein assemblies in response to genotoxic stress. Although much remains to be learned about these types of cooperative and highly dynamic interactions and their functional roles, the rapidly growing interest in material properties of biomolecular condensates and in concepts from polymer chemistry and soft matter physics to understand biological processes at different scales holds great promises. Here, we discuss nuclear condensates in the context of genome integrity maintenance, highlighting the cooperative potential between clustered stoichiometric binding and phase separation. Rather than viewing them as opposing scenarios, their combined effects can balance structural specificity with favorable physicochemical properties relevant for the regulation and function of multilayered nuclear condensates.